The Nostrums of Common Sense - McKenna, Tony (International Gramsci Journal, 2023)
This article provides a Marxist analysis of the concept of ‘common sense’. It traces the evolution of this concept – through various philosophers from Aristotle to Thomas Paine – in order to throw light on Gramsci’s own radical mobilization of the notion of ‘common sense’ as a mode of thought, and the role it plays in his broader philo-sophical system of class consciousness and hegemony. The piece seeks to both appreciate the revolutionary aspects of Gramsci’s analysis of ‘common sense’ but also to draw attention to some of its limitations. Building on this, the final part examines the way in which ‘common sense’ as a concept has been mobilized – contra Gramsci – by the ruling classes of our own epoch; how it becomes a key component in the ‘political correctness gone mad’ narrative and a way, therefore, of justifying some of the most reactionary initiatives – from the xenophobia which feeds anti-immigrant bigotry to the neoliberal austerity measures which have flayed the living standards of those at the bottom in order to enshrine the wealth of those at the top.